Study on Impact of Various Void Conditions on Shallow Rectangular Masonry-Concrete Power Tunnel and Surrounding Roads - Gang Tian; Chunfeng Jin; Haijun Zhang; Hai Shi; Yanqing Du; Yanli Qi; Mingzhou Bai (Advances in Civil Engineering)
To solve the problem of a potential void near a shallow rectangular masonry-concrete power tunnel, the ground-penetrating radar (GPR) detection technology is used and multiple GPR detection lines are placed to detect concealed void. The GPR images of circular and square voids are obtained, which can help increase accuracy of void identification. The models that cover 9 circular voids and 9 square voids are created to investigate how various forms and positions of void will affect the internal forces of the power tunnel structure and surrounding roads. In terms of morphological characteristics, according to the research results, the impact of a circular void on tunnel and surrounding roads is slightly stronger than that of a square void. If the circular void and square void are at 135° and 115°, respectively, the maximum shear force of the tunnel structure occurs at the floor. If both circular and square voids are at 115°, the maximum axial force of tunnel structure occurs at the right side wall. If both circular and square voids are at 135°, the maximum bending moment of tunnel structure occurs at the floor. If both circular and square voids are at 155°, the ground settlement and pavement stress of surrounding roads are maximized. Generally, if a void occurs at the middle or lower part of the side wall or near the side of the floor in a shallow rectangular masonry-concrete power tunnel, its adverse impact is at its worst. Therefore, GPR detection of the voids at the lower and middle parts and the side of the floor in the power tunnel should be intensified, in order to eliminate the risk of a void near power tunnel.